Life cycle prediction for agile supply chains: a comparison of methods - Aktas, Emel; Chomachaei, Fahimeh; Golmohammadi, Davood (Emerald, 2023)
The aim of this paper is to compare the performance of several product life cycle models on an empirical dataset from a lighting products retailer to inform inventory decisions for products that are in different life cycle stages: introduction, growth, maturity, or decline. Bass diffusion curves, piece-wise linear curves, and polynomial curves, fourth order polynomial curves are used to predict the life cycles of 2,618 products. We identify which products need an efficient and which require an agile supply chain design. We provide recommendations for how much inventory to keep, especially for products that are in the decline stage.
Keywords: bass diffusion model; piece-wise linear curves; life cycle prediction